Control Over the Morphology of Electrospun Microfibrous Mats of a Polymer of Intrinsic Microporosity - Elsa Lasseuguette; Richard Malpass-Evans; John M. Tobin; Neil B. McKeown; Maria-Chiara Ferrari (Membranes, 2021)
This study reports for the first time the preparation of an electrospun microfibrous mat of PIM-EA-TB. The electrospinning was carried out using a chloroform/n-Propyl-lactate (n-PL) binary solvent system with different chloroform/nPL ratios, in order to control the morphology of the microfibres. With pure chloroform, porous and dumbbell shape fibres were obtained whereas, with the addition on n-PL, circular and thinner fibres have been produced due to the higher boiling point and the higher conductivity of n-PL. The electrospinning process conditions were investigated to evaluate their impact on the fibres’ morphology. These microfibrous mats presented potential to be used as breathable/waterproof materials, with a pore diameter of 11 μm, an air resistance of 25.10−7 m−1 and water breakthrough pressure of 50 mBar.